Rancangan Mobile Ad-Hoc Networks untuk Solusi Jaringan Komunikasi Antar Armada Bergerak menggunakan Simulasi NS - Cahyadi, Widya (e-Jurnal Arus Elektro Indonesia, 2015)
AbstractThis paper proposed a route for a design of protocol that is considered appropriate to be applied as a solution to the communication networks between mobile fleet. The proposed protokol is AODV. The purpose of this protocol is able to expand the scope of these communications services, routing protocol techniques that fit the needs of that channel on VHF frequencies which have a low bitrate and narrow canal, with the consideration of the chosen AODV algorithm, use routing table with one entry for each destination without using source route, AODV relies on routing table to spread the Route Reply (RREP) back to the source and sequentially will direct the data packets to the destination. Based on the simulation results indicate that there are five nodes (0,1,2,3,4) nodes are mutually move (Mobile) where are node 0 will be connected to node 4, and then make the node 2 (nearest) as a relay link between node 0 to node 4, AODV protocol is a reactive routing protocol, which is only to request a route when needed.Keywordsâ Mobile Ad hoc NETwork (MANET), Network Simulator (NS), Routing Protocol